Mapping of mental health care facilities and psychiatrists in a North Indian district of India - Aninda Debnath; Harshal Ramesh Salve; Rajesh Sagar; Anand Krishnan; Rakesh Kumar; Shashi Kant (Indian Journal of Psychiatry)
Introduction: Since 1990, the proportional contribution of mental disorders to India’s total disease burden has nearly doubled, but the number of psychiatrists has not increased proportionately. Even after two decades of District Mental Health Programme (DMHP) launch, a considerable treatment gap still exists for mental illness. The present study aimed to map all health facilities providing mental health services and all psychiatrists in district Faridabad, Haryana. Methods: The starting point was the information available with the DMHP and district health office. This was supplemented by web search and snowball sampling. All identified facilities were visited to map the mental health services provided. All the mental health care providers and health care facilities were mapped using “Google my Maps”. 2011 census data on population were used. Results: In Faridabad, 0.88 psychiatrists per lakh population were present. Most psychiatrists were concentrated in the urban area. The number of psychiatrists per lakh population was 1.1 in urban, compared to 0.54 in rural Faridabad. Clustering of mental health facilities was also observed more in urban areas (8.7 per 100 Sq Km) compared to rural areas (0.95 per 100 Sq Km) of district Faridabad. Conclusion: There was a scarcity of psychiatric manpower and facilities in the district with a distinct urban skew.